Analisis Simbol Budaya dalam Puisi Lisan Tinilo Paita di Kecamatan Lemito Kabupeten Pohuwato - Lahay, Tian Maya kartika; Hinta, Ellyana; Didipu, Herman (Reduplikasi: Jurnal Penelitian Pendidikan Bahasa Indonesia, 2021)
ANALYSIS OF CULTURAL SYMBOLS IN TINILO PA'ITA ORAL POEM IN LEMITO DISTRICT, POHUWATO REGENCYTian Maya Kartika Lahay1, Ellyana Hinta2, Herman Didipu3.Â Study Program of Language and Literature Education Faculty of Letters and Cultures, Universitas Negeri Gorontalo*corresponding tiankartika11@gmail.comUniversitas Negeri Gorontalo ellyana.hinta@yahoo.comUniversitas Negeri Gorontalo herdi.ung@gmail.comABSTRACTThis research was focused on symbols. According to Dharmojo, symbols are divided into two, namely verbal and nonverbal symbols. The theory of semiotics focuses on the study of symbols that give meaning to the text and culture in the traditional Tinilo Pa'ita ceremony, so this study was conducted using a qualitative approach with descriptive research. The data of this research were verbal and nonverbal symbols in Tinilo Pa'ita oral poetry which were obtained from the text and a set of objects in the Tinilo Pa'ita traditional ceremony. Furthermore, in data collection using a literature review technique, which goes through the stages of determining the text, reading, identifying, recording, describing, and concluding, observing, conducting documentation techniques, and conducting interviews. The results of this study indicated that Tinilo Pa'ita's oral poem is an oral poem that also contains verbal and nonverbal symbols. Verbal symbols contained in the Tinilo Paita script and nonverbal symbols are found in a set of tools used in the traditional Tinilo Pa'ita ceremony. In verbal symbols there are many words that have various meanings, where each word contained has a different meaning from what the people of Gorontalo know in general. This can be seen from the research conducted by researchers.Â Keywords: Tinilo Pa'ita, semiotic theory, verbal symbols, nonverbal symbols